SiTelinga sebagai Inovasi Layanan KTP-El Ramah Disabilitas Tuna Rungu Berbasis Keadilan Fiqih Syari’ah di Kota Palangka Raya - Muhammad Diky Andreyansyah; Surya Sukti; Novita Mayasari (Jayapangus Press, 2025)
Persons with hearing disabilities in Palangka Raya continue to face obstacles in accessing Electronic Identity Card (KTP-El) services, particularly due to communication barriers and the limited availability of disability-friendly facilities. This study aims to formulate an innovative KTP-El service model based on the principles of Islamic jurisprudential justice through the development of “SiTelinga,” a system designed to accommodate the specific needs of the hearing-impaired. A qualitative approach was employed using a literature study of population administration regulations and Islamic legal concepts related to justice and ease (raf‘u al-haraj). The findings indicate that the service innovations developed—such as enhanced visual communication, sign language interpreter support, staff training, and disability-inclusive service programs—effectively reduce communication barriers and improve service quality. From the perspective of Islamic jurisprudence, these innovations align with the principles of al-‘adalah (justice), al-masyaqqah tajlibu al-taysīr (facilitating ease in the presence of hardship), and the objectives of maqāṣid al-sharī‘ah in safeguarding public welfare. In conclusion, SiTelinga has the potential to serve as an inclusive KTP-El service model for persons with hearing disabilities grounded in Islamic jurisprudential justice, offering not only alignment with Islamic ethical principles but also a promising contribution to the development of inclusive public services in other regions.